2005
DOI: 10.1111/j.1467-9582.2005.00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐focus prosodic phrase boundaries in Tokyo Japanese: asymmetric behavior of an f0 cue and domain‐final lengthening*

Abstract: The present study shows an asymmetric behaviour between an F0 cue and a durational cue in a post-FOCUS part of an utterance in Tokyo Japanese. Though F0 resetting which marks the left edge of a Major Phonological Phrase is missing at the left edge of a post-FOCUS clause boundary, word-final lengthening which marks the right edge of an Intonational Phrase is retained there. Based on this observation, Headless Post-FOCUS IP Structure is proposed, and such prosodic structure is argued to be compatible with not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Some have proposed that just one level in between is enough, e.g., phonological phrase (English: Nespor and Vogel, 1986;Turkish: Ipek and Jun, 2013;Japanese: Ishihara, 2011). Some are in favor of two levels, e.g., major phonological phrase and minor phonological phrase (Japanese: Kubozono, 1993, andSugahara, 2005;English: Selkirk, 2005, andSelkirk et al, 2004), which are roughly equivalent to intermediate phrase and pitch accent phrase as proposed by Beckman and Pierrehumbert (1986). More recently, Ito and Mester (2013) proposed that major and minor phrase can be integrated into one category, namely φ-phrase, because they both serve as the domain of downstep and initial lowering.…”
Section: Boundary Markingmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have proposed that just one level in between is enough, e.g., phonological phrase (English: Nespor and Vogel, 1986;Turkish: Ipek and Jun, 2013;Japanese: Ishihara, 2011). Some are in favor of two levels, e.g., major phonological phrase and minor phonological phrase (Japanese: Kubozono, 1993, andSugahara, 2005;English: Selkirk, 2005, andSelkirk et al, 2004), which are roughly equivalent to intermediate phrase and pitch accent phrase as proposed by Beckman and Pierrehumbert (1986). More recently, Ito and Mester (2013) proposed that major and minor phrase can be integrated into one category, namely φ-phrase, because they both serve as the domain of downstep and initial lowering.…”
Section: Boundary Markingmentioning
confidence: 99%
“…There has been rich empirical evidence that in many languages focus is realized mainly by increasing the pitch range, intensity, duration, and articulatory fullness of the focused word, and reducing the F 0 and intensity of the following words, while leaving the prefocus words largely unchanged (English: Cooper et al, 1985;de Jong, 1995;Xu and Xu, 2005;Mandarin: Chen and Gussenhoven, 2008;Xu, 1999;German: Féry and Kügler, 2008;Greek: Botinis et al, 1999;Dutch: Swerts et al, 2002;Japanese: Ishihara, 2002; Korean: Lee and Xu, 2010;Turkish: Ipek, 2011;Tibetan: Wang et al, 2012;Zhang et al, 2012;Estonian: Sahkai et al, 2013). The reduction of postfocus F 0 and intensity is known as postfocus compression or PFC , and it is found to be critical for focus perception in at least some of these languages (Vainio et al, 2003, for Finnish;Rump and Collier, 1996, for Dutch;Prom-on et al, 2009, for English;Ishihara, 2011, andSugahara, 2005, for Japanese; Xu, 2005, andXu et al, 2012, for Mandarin). What is yet unclear, and in fact rarely asked, is how extensive the temporal domain of PFC is.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this view, experimental evidence has shown that speakers can indeed employ prosodic cues when their language has other means to signal focus. Consider the case of Mandarin Chinese and Japanese: In both of these languages, focus can also be marked via focus-sensitive particles or phrasing, but speakers have been shown to effect focus using prosodic parameters such as pitch and duration [5,6,7]. Moreover, both languages manage to employ prosody for focus expression in ways that do not interfere with the production of lexical tones or pitch accents (e.g., by expansion of pitch register).…”
Section: Introductionmentioning
confidence: 99%
“…Other consequences (such as the deletion of later beats of prominence in the focus domain or the insertion or deletion of prosodic boundaries) are derived indirectly from the resulting change in prominence relations under this suggestion. This perspective is pursued in interesting ways in Selkirk (2002Selkirk ( , 2004, Sugahara (2005) and Bü ring (2009).…”
Section: The Specific Effects Of [F] On the Prosodic Structurementioning
confidence: 99%